SUBSTANTIAL FACTORS IN CHANGING THE NAMING SYSTEM OF TRADITIONAL MAKASSAR ETHNIC SOCIETY TO MODERN - Munira Hasjim (Sekolah Tinggi Pariwisata Mataram, 2022)
This paper reviews the changes in the nomenclature system of the traditional Makassar ethnic community to the modern one. The goal is to know the factors behind the name change process. This study uses the Grounded Research method, a descriptive-analytic approach to capture and analyze data. The population of this research is Makassar people who are defined as native speakers of the Makassar language and who are domiciled in the Makassar community and have Makassarese parents. The sample of this study amounted to 260 people, who were determined purposively based on the distribution of administrative areas in the areas inhabited by the Makassar ethnic community. The study indicates that the factors that influence the occurrence of these changes are geographical factors, historical, language, and culture; advances in technology and media; parent education level factors; demographic and social characteristics; factor orientation to the future; and prestige factors.